DNA conformational changes induced by cationic gemini surfactants: the key to switching DNA compact structures into elongated forms1. Issue 37 (25th April 2015) - Grueso, Elia; Kuliszewska, Edyta; Roldan, Emilio; Perez-Tejeda, Pilar; Prado-Gotor, Rafael; Brecker, Lothar
<x xml:space="preserve">Abstract</x> The extent of DNA decompaction induced by m-s-m gemini surfactants depend on the surfactant's tail length and on spacer's length.